2020
DOI: 10.1159/000509568
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Aesthetic Results after Immediate Breast Reconstruction Using Human Acellular Dermal Matrices: Results of a Multicenter, Prospective, Observational NOGGO-AWOGyn Study

Abstract: <b><i>Background:</i></b> With the increased use of acellular dermal matrices (ADMs) in implant-based breast reconstructions (IBBRs), the evaluation of patient-reported outcomes becomes more important. <b><i>Methods:</i></b> Patients who underwent an immediate human ADM-assisted, submuscular IBBR were included in this noninterventional, multicenter, prospective cohort study. Patients with primary reconstruction (cohort A) and patients with a revision surgery afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…10,[19][20][21][22] This review also included published measures of breast reconstruction patient-reported outcomes (PROs) to provide an initial conceptual model. 4,[23][24][25][26] Semistructured interviews were then conducted using an interview guide that incorporated concepts and themes identified in systematic reviews of breast reconstruction PROMs. [27][28][29] Interviews were designed to explore concepts relevant to quality of life, satisfaction, functional and aesthetic outcomes, mental health, and barriers to access.…”
Section: Phase I Conceptual Framework Formulationmentioning
confidence: 99%
“…10,[19][20][21][22] This review also included published measures of breast reconstruction patient-reported outcomes (PROs) to provide an initial conceptual model. 4,[23][24][25][26] Semistructured interviews were then conducted using an interview guide that incorporated concepts and themes identified in systematic reviews of breast reconstruction PROMs. [27][28][29] Interviews were designed to explore concepts relevant to quality of life, satisfaction, functional and aesthetic outcomes, mental health, and barriers to access.…”
Section: Phase I Conceptual Framework Formulationmentioning
confidence: 99%